Whole-plant forage and grain sorghums and corn silages for growing cattle - Kirch, B.; Hamma, S.; Bolsen, K.; Hoover, J.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials were conducted to determine the feeding value of whole-plant forage sorghum, grain sorghum, and corn silages, with and without 25% rolled grain sorghum added to the ration. In general, growing cattle fed corn or grain sorghum silages out-performed those fed forage sorghum silages. Only forage sorghums with moderate grain yields supported gains approaching those from grain sorghum silages. With the addition of 25% rolled grain sorghum, cattle performance from the low and medium grain-yielding forage sorghum silages was improved greatly (gains by 20 to 44%, dry matter intake by 12 to 17%, feed conversion by 4 to 25%). Adding 25%grain to the moderate grain-yielding forage sorghum hybrid rations increased cattle gains to a level comparable to those from grain sorghum silages. These studies indicate that the grain content of a corn or sorghum silage ration is the major determinant of cattle performance, and that Whole-plant corn and grain sorghums should produce the fastest and most efficient gains in growing programs.
Keywords: Beef; Forage; Grain sorghum; Corn silages; Growing cattle